Philippines : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
The Country Procurement Assessment Report (CPAR) is an analytical tool, intended to assess the public procurement system, in this case, in the Philippines, and, in the process, generate a dialogue with the Government on reforms needed. This CPAR assessment was conducted from October 2001 to June 2002, and part of an integrated comprehensive Public Expenditures, Procurement, and Financial Management Review. Despite existing laws and regulations, Executive and Administrative orders, there was the absence of an omnibus procurement law. The specific purpose of the CPAR was to establish the need for procurement reform, provide guidance for procuring goods, works, and consulting services, through a comprehensive analysis of the public sector procurement system, legal framework, the organizational structure, and capabilities, in addition to an assessment of institutional and organizational issues related with the procurement process. Further activities included the development of an action plan to enhance the institutional framework, and, the assessment of the competitiveness and performance of the local private industry related to its participation in public procurement. The main recommendation - the passage of a procurement law - was initiated when Congress passed the Government Procurement Act (2002), and signed into law in January 2003. Implementing rules and regulations are under preparation, but it should be mentioned that this step constitutes a major reform, towards significant budgetary savings, and an accountable procurement process.